Schelkunoff array synthesis methods using adaptive-iterative algorithm - Abdul Latiff, Nurul Mu'azzah (2003)
The adaptive-iterative algorithm is an error-reduction algorithm that has been extensively studied in recent years. Basically, this algorithm is a combination of iterative algorithm with adaptive algorithm. By the co-emergence of these algorithms, a better performance and wider application are hoped to be achieved since each of these algorithms has its own advantages respectively. Although considerable research has been devoted to apply this algorithm in variety of DSP applications such as filter design and signal reconstruction, rather less attention has been paid for application in antenna array synthesis. For that reason, it is the purpose of this thesis to outline the implementation and use of adaptive-iterative algorithm in designing antenna array. In doing sa, Schelkunoff Polynomial Method will be used in order to have z-domain information. Intended to achieve the aim of this project, MATLAB program will be employed to present the outcomes of modulus reconstruction on antenna array using adaptive-iterative algorithm. The results and performance of other error-reduction algorithm such as Papoulis algorithm and optimal algorithm are also presented and discussed in this thesis, along with the discussion of adaptive-iterative algorithm for comparison purposes.